Assessing HIV/AIDS patients’ access to antiretroviral drugs using the healthcare accessibility framework: a cross-sectional study from Shandong, China - Zhixin Fan; Songlin Zheng; Weiming Cui; Chao Zheng; Qiang Sun; Jia Yin (BMC Infectious Diseases)
Abstract Background Antiretroviral drugs are important for HIV/AIDS patients, but we know little about the real-life barriers patients face in accessing them. Following the Levesque framework, this study described the five abilities of HIV/AIDS patients in Shandong Province to perceive, to seek, to reach, to pay and to engage in accessing antiretroviral drugs and the factors associated with them. Methods A cross-sectional questionnaire survey, using convenience sampling, was conducted among HIV/AIDS patients in three AIDS-designated hospitals in Shandong Province. We used catastrophic cost methods and the HIV Treatment Adherence Self-efficacy Scale to assess patients' ability to pay and engage, respectively. Results A total of 301 participants completed the questionnaire, with 20.9% having a CD4 cell count of less than 200 cells/µL. For the ability to perceive, only 16.6% of respondents self-reported low knowledge of HIV progression and medication. For the ability to seek, 24.3% self-reported having experienced social discrimination, and 21.9% reported 'choosing not to seek health insurance reimbursement due to fear of privacy disclosure. For the ability to reach, the average time spent on purchasing drugs was 2.1 ± 1.3 h, with respondents living in rural areas and having low levels of education most likely to spend more hours. For the ability to pay, the overall incidence of catastrophic health expenditures for drugs was 28.9%. For the ability to engage, the overall median score on the HIV-ASES scale was 118.0 (IQR: 107–120), and 69.4% had high treatment compliance. Respondents who experienced drug toxicities were more likely to have poorer treatment compliance (OR = 2.12, P = 0.011). Conclusions In general, access to antiretroviral drugs for HIV/AIDS patients was relatively good, while their ability to reach and pay was unsatisfactory. There should be a great concern for health education intervention and geographical accessibility of antiretroviral drugs in healthcare institutions. Policy should focus on the impact of social discrimination and drug toxicity on access to antiretroviral drugs.